(untitled) (Revista de Ciências Agroveterinárias, 2004)
The historical evolution of curricula from the Veterinary Medicine course from Santa Catarina State University (UDESC), Brazil, is presented. Using documental sources, the curricular structures were examined, from its first version, implemented in 1973, to the last one, that follows the norms for the minimal curriculum for veterinary education aproved by the federal resolution 10/84. The main areas of action from Veterinary Medicine - corresponding to the curricular subjects of the course - were related with the epistemological category “style of thought” proposed by L. Fleck. It was observed that the curricular grids experienced very few significant changes with the conclusion that the course is based on the early 80’s Veterinary Medicine thinking.